ANALYSIS OF BATHYMETRIC DATA UTILIZATION FOR UNDERWATER MORPHOLOGY VISUALIZATION IN JEMAJA ANAMBAS ISLANDS RIAU ISLANDS INDONESIA - Bayu Dwi Santoso; Puspita Indra Wardhani; Ratih Puspita Dewi; Fitra Annurhutami (Universitas Sebelas Maret (UNS), 2024)
Administratively, Pulau Jemaja is located in the Kepulauan Anambas Regency, Riau Islands Province, which lies between 2°10'0